2019
DOI: 10.1016/j.jcis.2018.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential of superhydrophobic nanoporous alumina membranes for direct contact membrane distillation

Abstract: The average vapor fluxes, J, across three sets of AAO membranes with average nanochannel diameters (and porosities) centered at 80 nm (32%), 100 nm (37%), and 160 nm (57%) varied by < 25%, while we had expected them to scale with the porosities. Our multiscale simulations unveiled how the high thermal conductivity of the AAO membranes reduced the effective temperature drive for the mass transfer. Our results highlight the limitations of AAO membranes for DCMD and might advance the rational development of desal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 70 publications
(67 reference statements)
1
26
0
Order By: Relevance
“…The thermal conductivity of the membrane surface must be as low as possible [51] Fouling resistance The polymeric membrane can be coated with fouling resistant materials to ensure high permeate flux [52] Thermal stability The MD polymeric membrane must show high thermal stability up to 80 • C. [53] Chemical resistance The MD membranes must exhibit good chemical resistance because they may come in contact with acids and bases [54] 4.…”
Section: Layersmentioning
confidence: 99%
“…The thermal conductivity of the membrane surface must be as low as possible [51] Fouling resistance The polymeric membrane can be coated with fouling resistant materials to ensure high permeate flux [52] Thermal stability The MD polymeric membrane must show high thermal stability up to 80 • C. [53] Chemical resistance The MD membranes must exhibit good chemical resistance because they may come in contact with acids and bases [54] 4.…”
Section: Layersmentioning
confidence: 99%
“…Also, it has been demonstrated that intrinsically wetting materials with reentrant cavities can entrap air upon immersion in wetting liquids, and thus, achieve the function of omniphobic surfaces. Based on this body of work 27,28,29,30 and previous experience with DCMD 31 , we decided to create membranes that have pores with reentrant inlets and outlets. It was envisioned that such a membrane could entrap air upon immersion in wetting liquids due to its microtexture, giving rise to the idea of GEMs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the experimental set-up with silica-GEMs suffered from what is known as temperature polarization, wherein the hot side loses heat to the cold side, lowering the flux31 .…”
mentioning
confidence: 99%
“…It is a thermally-driven separation process, in which only vapors transfer through a microporous hydrophobic membrane [3,[5][6][7]. MD membranes are made of hydrophobic polymeric materials such as polyvinylidene fluoride (PVDF), polypropylene, and polytetrafluorethylene (PTFE) [4,[8][9][10][11][12]. MD can treat high salinity feed solutions that RO cannot, including RO brine and wastewaters from shale gas industry [6,7,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane wetting is generally observed during the long-term operation of the MD process [24]. Factors affecting membrane wetting include transmembrane pressure, capillary condensation, scale deposition (inorganic fouling), organic fouling, surfactants, and membrane degradation [8,19,23,25]. The membrane wetting reduces the quality of product water and changes the flux through the membrane [21,26].…”
Section: Introductionmentioning
confidence: 99%